P-517 Validating reference gene expression stability in human ovarian follicles, oocytes, cumulus cells, ovarian medulla, and ovarian cortex tissue. (30th June 2022) - Cadenas, J; Pors, S; Nikiforov, D; Zheng, M; Subiran, C; Bøtjær, J; Mamsen, L; Kristensen, S; Andersen, C
Abstract: Study question: How does the expression stability of commonly used reference genes (RG) vary in different human ovarian cells and tissues? Summary answer: The RG stability differed among human ovarian cell types and tissues, but an RG with high stability was identified for each cell and tissue type. What is known already: The expression of RGs used to normalize RT-qPCR may vary between different tissues, cell types, and experimental conditions. Hence, selecting the most appropriate RGs is critical in any experimental design to interpret data generated by RT-qPCR with the best accuracy. Human ovarian cells are phenotypically very different and often only available in limited amounts. In several animal species RG expression stability has been validated in oocytes and other ovarian cells, however, the suitability of a single universal RG in the different human ovarian cells and tissues has not been determined. Study design, size, duration: This is an experimental study performed at a university hospital from January 2021 to September 2021. Participants/materials, setting, methods: The freely available NormFinder software was used to analyze the expression stability of five commonly used RGs ( GAPDH, B2M, RPLP0, ACTB, and PPIA ) in human oocytes (n = 160), preantral follicles (n = 160), cumulus cells (n = 13), ovarian medulla (n = 8), and ovarian cortex tissue (n = 60). Samples were collected from 29 patients (aged 28 years on average; range 14–36) undergoing unilateral oophorectomy and ovarian tissue cryopreservation for fertility preservation. Main results and the role of chance: The Normfinder software identified ACTB as the best RG for oocytes and cumulus cells; and B2M for medulla tissue and isolated follicles. Overall, comparisons of the cycle threshold (Ct) values demonstrated a wide variation among the RGs within the same group of samples (P < 0.05), especially for oocytes and preantral follicles with normalized RNA. The genes ACTB and RPLP0 showed the highest levels of expression and PPIA the lowest levels of expression in all types of samples, except for cortex tissue, where PPIA had the highest level of expression and B2M the lowest. These results infer that different results could be obtained when using different RGs for data normalization. The combination of two RGs only marginally increased stability, indicating that using a single validated RG would be sufficient when the available testing material is limited. For cultured ovarian cortex culture, GAPDH or ACTB were found to be the most stable genes depending on culture conditions. Limitations, reasons for caution: Since human oocytes are scarce and contain a small amount of RNA, only five RGs were evaluated. Moreover, only germinal vesicle (GV) oocytes and preantral follicles (60-80 µm) were tested. Future studies may validate other genes and investigate the effect of oocyte maturation and follicle growth on RG stability. Wider implications of the findings: Our findings highlight the importance of validating RGs for each cell type or tissue and culture condition. Hence, our results can be of use as guidance for future studies involving gene expression analyses in human ovarian cells and tissues, including oocytes and preantral follicles. Trial registration number: Not applicable